Functional connectivity differences in healthy individuals with different well-being states - Akshita Joshi; Divesh Thaploo; Henriette Hornstein; Yun-Ting Chao; Vanda Faria; Jonathan Warr; Thomas Hummel (Neuroscience Informatics, 2023)
Well-being (WB) is defined as a healthy state of mind and body. It is a state in which an individual is able to contribute to its society, able to work productively and overcome the normal stress of life. WB is a multi-dimensional concept and covers different aspects, including life satisfaction and quality of life. Little is known as to whether there are differences in connectivity patterns between healthy individuals with different WB states. We evaluated the WB state of healthy individuals with no prior diagnosis of any psychological disorder using the “General habitual WB questionnaire”, covering mental, physical and social domains. Subjects with mean age 25±4 years were divided into two groups, high WB state (n = 18) and low WB state (n = 14). We investigated and compared the groups for their resting state (rs-fMRI) functional connectivity (FC) patterns using DPARSF compiled with SPM12 toolbox. WB specific seeds were chosen for FC analysis. In the high WB group we found significantly increased connectivity between bilateral angular gyrus and frontal regions comprising the orbitofrontal cortex (OFC), right frontal superior gyrus and left precuneus. The low-WB group showed increased connectivity between the bilateral amygdala and the occipital lobe and the right anterior OFC. To conclude connectivity results with a quantitative approach, suggest differences in cognitive and decision-making processing between people with varying WB states. The high-WB group when compared to low-WB group had higher cognitive processing and decision making based on their internal mental processes and self-referential processing, whereas connectivity between amygdala and OFC relates to decreased attentional processing and promotes effective emotional regulation that may be a lead to rumination.